An update on the process economics of biogas in South Africa based on observations from recent Installations - Nagel, Brigette Mariana (Department of Chemical Engineering, 2020)
This dissertation investigates, in the context of South Africa (SA), the process economics of energy from biogas, and hence the financial viability establishing a biogas plant in the absence of a formal incentivisation programme. Firstly, the study set out to establish an improved understanding of the costs associated with the technology. Data on the capital- and running costs of existing biogas plants in SA were sourced by means of stakeholder interviews, and compared with published data on similar plants in countries where the biogas sector is more mature. Two biogas usage pathways were evaluated: biogas-to-electricity through a Combined Heat and Power (CHP) system, and biogas-to-biomethane. Regression analysis was carried out on the observed costs, and this was used to predict future costs. A capacity-cost factor of 0.68 for biogas-to-electricity and 0.57 for biogas-tobiomethane was obtained. Statistical hypothesis testing revealed that the values are significantly smaller than 1, which indicates that economies of scale are observed in both cases. A Lang factor of 1.81 was determined, based on cost data from 20 medium- to large scale biogas plants in South Africa. Operational and Maintenance costs were determined to vary between R2.6 – R4.6 per Nm3 biogas produced where significant feedstock sorting and/or transport costs are present and R0.3 – R1.4 per Nm3 biogas produced where minimal feedstock sorting and/or transport costs are present. It was observed that energy can be recovered from biogas plants at a Levelised Cost of Energy (LCOE) of 0.5 – 2 R/kWh in SA, which corresponds with the range of 1.8 – 2.8 R/kWh documented internationally, even though the LCOE in SA is generally lower that what is observed abroad, especially at plant capacities greater than 1 MW. Based on a financial analysis, a positive Net Present Value (NPV) for a medium-cost CHP plant where only electricity is utilised as income stream is possible from 0.3 MWe upward, with greater returns at higher plant capacities. For a biomethane plant, a positive NPV can be attained at plant capacities of 4 MWeq and higher. A comparison on the financial benefits of two different biogas usage pathways revealed that a biomethane plant has greater potential profitability than a CHP plant at capacities greater than 5 MWeq, whereas at smaller capacities, a CHP plant would yield better returns. The most attractive investment scenario evaluated was a 6 MWeq biomethane plant, where a Return on Investment (ROI) of 18% could be attained with a payback period of 8 years for a plant lifetime of 20 years. However, a risk analysis making use of Monte Carlo simulation revealed that such a project will only have an 91% chance of obtaining a positive NPV, which is below the set benchmark of 95%. Considering the high up-front capital investment associated with a large scale biogas project, it is anticipated that the financial risks associated with such a project would be too high to merit investment at current conditions in South Africa. This could, however, be mitigated if an additional income stream could be established in the form of an incentive, subsidy, grant, or alternatively a waste treatment gate-fee or fertiliser sales income. Lastly, if electricity and fuel prices in South Africa continue to increase at the rate observed over the past two decades, the business case for a single-income-stream biogas plant will become increasingly attractive and profitable in the near future.